*Note:- 1) If y = cosx ; then dy/dx = -sinx*

*2) If y = sinx ; then dy/dx = cosx*

*3) If y = u*v ; where both u & v are functions of 'x' , then*

*dy/dx = u*(dv/dx) + v*(du/dx)*

*4) If y = k ; where 'k' = constant ; then dy/dx = 0*

Now, the given function is :-

cos(x*y) = 1 + siny

Differentiating both sides w.r.t 'x' we get

-sin(xy)*[y + x*(dy/dx)] = cosy*(dy/dx)

or, -y*sin(xy) -x*sin(xy)*(dy/dx) = cosy*(dy/dx)

or, -y*sin(xy) = (dy/dx)*[cosy + x*sin(xy)]

or, dy/dx = [-y*sin(xy)]/[cosy + x*sin(xy)]

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now